Axial spondyloarthritis in India: determining the delay in diagnosis, impact on work productivity, and attitude of patients toward treatment - Kamini Narendra Reddy; Asawari Raut; Pravin Patil (Indian Journal of Rheumatology)
Background: Axial spondyloarthritis (axSpA) primarily affects young, working demographics, and impacts on work productivity. Here, we aimed to determine the delay in diagnosis of axSpA, assess the impact on work productivity, and explore patients' perception of available treatment options. Methodology: A cross-sectional study was conducted on 100 axSpA patients who fulfilled the ASAS criteria. Ethical approval was obtained. Data regarding disease duration, delay in diagnosis, and other demographics were collected using an investigator-designed questionnaire. Disease activity, quality of life, and loss in work productivity were determined using standardized scales. Results: Median disease duration and delay in diagnosis were 5 years (interquartile range [IQR]: 2.0, 10.0) and 2 years (IQR: 0.5, 5.0), respectively. Median Bath Ankylosing Spondylitis Disease Activity Index, Bath Ankylosing Spondylitis Function Index, Bath Ankylosing Spondylitis Global, and Ankylosing Spondylitis Quality of Life scores were 4.15, 3.00, 4.00, and 8.00 respectively. Three different specialists were visited by 58% of the patients before reaching a rheumatologist. An incorrect clinical impression was made in 69% of the patients before consultation with the rheumatologist. Median presenteeism and impact on work productivity reported were 20% and 20.34%, respectively. Eight percent of the patients had to cease employment due to debilitating consequences of axSpA. Daily activities were affected up to 40%. A misconception that “allopathic medications cause side effects in all axSpA patients” was held by 58% of the patients and 25% of the patients believed that doctors deliberately conceal side effects of medications. Conclusion: A patient referral pathway for axSpA should be established to avoid the visits to multiple specialists. AxSpA not only reduces work productivity but also leads to work disability. There is a need to address the patient's concerns regarding modern medicine so that their health-seeking behavior is improved.